One-year cardiovascular risk and quality of life changes in participants of a health trainer service. (May 2014) - Gidlow, Christopher J; Cochrane, Thomas; Davey, Rachel; Beloe, Marion; Chambers, Ruth; Kumar, Jagdish; Mawby, Yvonne; Iqbal, Zafar
Aims: To explore 12-month changes in cardiovascular disease (CVD) risk and health-related quality of life (HRQoL) in participants of a health trainer (HT) programme. Methods: Participants were 994 adults with at least one established CVD risk factor who were referred to a HT programme. The primary outcome was 12-month change in Framingham 10 year CVD risk score. Secondary outcomes included change in individual risk factors and HRQoL. Intention to treat analysis was used to explore 12-month changes for the overall population and those classified 'high risk' (≥20% CVD risk) at baseline. Results: At baseline, 33.6% of participants were classified as 'high CVD risk' and 95.7% were overweight or obese. There were modest 12-month improvements in most modifiable CVD risk factors, but not overall CVD risk (-0.25±6.50%). In 'high-risk' participants significant reductions were evident for overall CVD risk (-2.34±8.13%) and individual risk factors. Small, significant 12-month HRQoL improvements were observed, but these were not associated with CVD risk change. Conclusions: Significant CVD risk reductions in participants in this HT programme with high baseline CVD risk (.20%) in HRQoL in the population as a whole indicated that the programme in its current form should target high-risk patients.